GEONICS (GEOMIMETICS) AS A TRANS-DISCIPLINARY RESEARCH DIRECTION - Valery S. Lesovik (Moscow Polytechnic University, 2016)
The paper is devoted to a new transGdisciplinary research direction - geonics (geomimetics). As distinct from biomimetics, this new discipline studies the basic principles of the development of inorganic world in order to optimize the system "man - material - environment". The article asserts that geonics must become the foundation for material scienceof the future.